SOCIAL SUPPORT FOR HEALTH ON INSTAGRAM: A DIGITAL ETHNOGRAPHIC STUDY - Widodo, Aan; Marta, Rustono Farady; Solihin, Mohammad; Sudarsono, Achmad Budiman; Engliana, Engliana (ASPIRATION Journal, 2023)
Social support practices are changing due to the presence of social media. Offline social support is marked by physical presence, while the presence of online support is through comment interactions that occur, including regional heads who are exposed to COVID-19. This article aims to explain online social support in interactions through uploads and comments on Instagram. The concept used is online social interaction and support. This research applied digital ethnography methods with online participant observation data collection techniques. The subject studied was the Instagram account @bimaaryasugiarto. The research results show that online social support appears in uploading and commenting activities. These results also confirm the three types of support that occurred, namely, informational, experiential, and emotional support, along with the four factors in emerging social support. The reactions and postings on Instagram contribute to forming many types of social support, namely online social support for health.